IMPROVING GRADUATE OUTCOMES THROUGH EFFECTIVE EDUCATIONAL FINANCE MANAGEMENT - Ihsan, Rifky Muhammad; Badrudin, Badrudin (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to examine the role of effective financial management in improving the quality of graduates in faculties at universities. Using qualitative research methods based on postpositivist ideology, this research uses inductive analysis to explore the natural state of objects, focusing on meaning rather than generalizations. The findings show that appropriate allocation of funds for the development and maintenance of educational infrastructure, such as laboratories, libraries and comfortable classrooms, is positively correlated with the quality of graduates. Additionally, effective financial management is directly related to the availability of educational resources. Stakeholder engagement, including government, society, and the private sector, plays a critical role in improving graduate outcomes. The research results show that graduates in faculties at universities are well prepared to enter the world of work, have a strong work ethic, and show a high level of creativity.